OVERVIEW OF ASPERGILLOSIS A FUNGAL DISEASE IN POULTRY AND ITS EFFECT ON POULTRY BUSINESS - Muhammad Hamza; Abdul Samad; Areeb Ahmer; Ayesha Muazzam; Sania Tariq; Kashif Hussain; Hafeez Ur Rehman Ali khera; Muhammad Umair Waqas (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Aspergillus fumigatus is the causative agent of the aspergiliousis and it is an infectious disease caused by the fungus. The infection is caused by the inspiration of fungal spores and these spores also contaminate the egg and are transferred from the egg shell. This disease is commonly occurred in the acute and chronic form. Acute form occurs when the birds inhale large no of fungal spores and the chronic form occurs when the birds are immuno suppressant or weak immune system. Anorexia, gasping sound, dyspnoea are the clinical signs of the disease. Pea size granulomas white to yellowish color are the gross lesions pulmonary blood vessel congestion is seen microscopy. History, necropsy, sign symptoms and history are used for the diagnosis of the disease cultures of the fungus and biochemical changes are also involved during this process. There is no proper treatment of this disease and the way to control this disease is its prevention. Prevention of wet litter and soil proper fumigation and disinfection of the poultry utensils feeding and watering line sanitization are the best methods to prevent the disease and helpful in its control.